1991
DOI: 10.2307/352743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corporal Punishment, Perceived Caretaker Warmth, and Cultural Beliefs on the Psychological Adjustment of Children in St. Kitts, West Indies

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. National Council on Family Relations is collaborating with JSTOR to digitize, preserve and extend access to Journal of Marriage and Family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 22 publications
3
40
1
1
Order By: Relevance
“…For example, McLoyd and Smith (2002) found that only in the context of low maternal support, but not high maternal support, spanking predicted an increase in mother-reported internalizing and externalizing problems over time for European American, African American, and Hispanic children from the National Longitudinal Survey of Youth. The present findings also extend Rohner’s (1986; Rohner et al, 1991) work on children’s perceptions of parental hostility as a mediator of the link between physical discipline and children’s adjustment by showing that the effects generalize to harsh verbal discipline and a cross-national context that makes possible the examination of cultural normativeness as a moderator of the mediated effect.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For example, McLoyd and Smith (2002) found that only in the context of low maternal support, but not high maternal support, spanking predicted an increase in mother-reported internalizing and externalizing problems over time for European American, African American, and Hispanic children from the National Longitudinal Survey of Youth. The present findings also extend Rohner’s (1986; Rohner et al, 1991) work on children’s perceptions of parental hostility as a mediator of the link between physical discipline and children’s adjustment by showing that the effects generalize to harsh verbal discipline and a cross-national context that makes possible the examination of cultural normativeness as a moderator of the mediated effect.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, Rohner, Kean, and Cournoyer (1991) found in a sample of 349 9- to 16-year-old youths from St. Kitts, West Indies that parents’ use of physical discipline negatively affects children’s adjustment in part through its effect on children’s perception of being rejected by their parents. In a meta-analysis of 43 studies with 7,563 participants from around the world, children’s perceptions of their parents’ acceptance and rejection were associated with children’s psychological adjustment in virtually every group tested (Khaleque & Rohner, 2002).…”
Section: Children’s Perceptions Of Maternal Hostility As a Mediator Omentioning
confidence: 93%
“…If children perceive spanking as a reasonable method of using parental authority, their behaviors may improve (Gunnoe & Mariner, 1997; Whaley, 2000). Indeed, the children’s perception of the punishment mediated the relationship between caregivers’ rejection and children’s psychological maladjustment (Rohner, Kean, & Cournoyer, 1991). The lack of parental support and involvement was more strongly associated with psychological maladjustment than was the use of physical punishment (Simons, Johnson, & Conger, 1994).…”
Section: Discipline and Children’s Social Competence And Behavior Promentioning
confidence: 99%
“…Rohner's (1986) parental acceptance-rejection theory posits that parenting behaviors affect a child's adjustment indirectly through the effects that they have on a child's perceptions of being rejected by his or her parents. The child's interpretation of his or her parent's behavior (that is, the meaning that a child makes of the parenting that he or she receives) depends on the cultural context (see Rohner, Kean, & Cournoyer, 1991). Within cultural contexts in which the use of physical discipline is normative, children whose parents physically discipline them may not perceive this discipline as being indicative of their parents' rejection of them, whereas children whose parents physically discipline them in a cultural context in which this behavior is not normative may perceive this experience as indicating their parents' personal rejection of them.…”
Section: Introductionmentioning
confidence: 99%